Cybercrime and cybersecurity in the Global South: concepts, strategies and frameworks for greater resilience - Donalds, Charlette (CRC Press, 2022)
Introduction: Cybersecurity and the Global South - solution-oriented reflections -- An exploration of country group differences in the global cybersecurity index -- Cybercrime in the Caribbean : risks, challenges and opportunities -- Privacy and security management : lessons from the enforcement of the EU general data protection regulation (GDPR) -- Cybersecurity policy compliance assessment : findings from government agencies in the Global South -- Cybersecurity compliance behaviour : exploring the influences of individual decision style and other antecedents -- Individual decision-making styles and employees' security compliance behaviour : reflections using an alternate lens -- Designing an effective cybersecurity programme in the organization for improved resilience -- The cybersecurity capability maturity model for sustainable security advantage -- An enhanced value-focused thinking methodology for addressing cybersecurity concerns -- Values of optimising cyber hygiene practices in MSMEs -- Toward a cybercrime classification ontology : a knowledge-based approach -- An integrated framework for developing and implementing a national cybersecurity strategy for Global South countries.